Austrian news coverage of Poland during the Polish EU presidency in 2011 - WÖHLERT, ROMY (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
This paper summarizes the key features of the Austrian print media news coverage of Poland throughout the timeframe of the Polish presidency of the EU in 2011. Results stem from a quantitative content analysis of three daily newspapers and one news magazine that were analyzed over a timeframe of 7 months from June 2011 to January 2012. Having entered the EU only in 1995, Austria is a rather young member state and one of the ‘EU-lightweights’, regarding its population size but also its political standing. Since its accession the country has developed a rather ambivalent and skeptical position towards its own EU membership as well as to EU-related matters, which is also strongly reflected in the focus of the Austrian news coverage of EU-related issues. At the same time, Austrian-Polish relations have specific features not only in a political, but also in a social, economic and historical dimension. Both aspects are crucial to bear in mind when Austrian news coverage of Poland during the presidency is taken into view. The paper shows that the Polish EU presidency did not change the overall thematic focus of the Austrian news coverage of Poland. Austrian news coverage shifted towards a more EU-related dimension only temporarily and slightly, but over- all, other frames of perception as well as characteristic news factors shaped the Aus- trian news coverage of Poland.